Performance evaluation and sensory acceptability of improved cooking banana varieties in low land areas of South Omo Zone, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Cooking banana is a type of banana mainly cultivated for its fruit, which is eaten as cooked as a vegetable in many food insecurity areas. The experiment was conducted at Dasenech Woreda where food insecurity and malnutrition is the main problem to evaluate the performance of cooking banana varieties for Fruit yield and boiling suitability. Four improved cooking banana verities (Cardaba, Nijiru, Matoke and Kitawira) were used as a treatment and arranged in RCBD with three replications. All the growth, agronomic and sensory acceptability data were subjected to analysis of variance (ANOVA) using SAS 9.0 computer software. The analysis of variance (ANOVA) revealed significant (P≤0.05) differences among the varieties on day of flowering, day of maturity, plant height, fruit weight, number of hands per bunch, bunch weight and total fruit yield. The early date flowering (112) and date of maturing (203.33), as well as the highest number of hands per bunch (8.66), were observed on the variety Matoke. The higher mean value of average fruit weight (168.33 g), bunch weight (15.66 kg) and total yield (23.46 ton ha-1) were observed on the variety Kitawira followed by Mattoke. For panelists scoring preference, the sensory acceptability means scores of boiled Mattoke, Cardoba and Nijru verities showed positive acceptability value from like slightly (Nijiru) to like very much (Mattoke) while Kitawara showed a negative acceptability level. Therefore, the variety Mattoke was identified as the early maturing, moderately yielder and best sensory quality accepted as compared to other varieties that could be recommended to demonstrate in the study area.Int. J. Agril. Res. Innov. Tech. 12(1): 161-165, June 2022